The effectiveness of negative-pressure wound therapy for wound healing after stoma reversal: a randomised control study (SR-PICO study) - Sohyun Kim; Sung Il Kang (Trials, 2020)
Abstract Background Although the wound-healing period for purse-string closure (PSC) after stoma reversal is longer than that required for the primary closure method, the rate of wound infection is reduced. The application of negative-pressure wound therapy (NPWT) can reduce the healing period for many types of wounds. Herein, we describe a planned trial to test the hypothesis that NPWT can reduce the healing period for PSC after stoma reversal. Methods/design Patients undergoing stoma reversal will be recruited and allocated into intervention and control groups, with 1:1 randomisation. Patients in the control group will receive standard postsurgical wound care; patients in the intervention group will receive NPWT using the PICO™ system. The target sample size will be 38 patients, as this will provide 80% power at the 5% level of significance to detect a 7-day reduction in the wound-healing period in the intervention group compared to that in the control group. The primary endpoint will be the duration to wound healing, defined as the time to nearly complete epithelisation of the wound, without any discharge or surgical site infection (SSI). Secondary endpoints will be the SSI rate, length of postoperative hospital stay, number of wound dressings and visits to the hospital for wound dressing after discharge, total cost of wound dressings, and patient and observer scar assessment scale scores. Discussion The results of this planned randomised controlled study will clarify the role of NPWT in patients undergoing stoma reversal and strengthen the rationale for choosing a dressing technique. Trial registration Clinical Research Information Service (CRIS), KCT0004063. Registered on 6 June 2019.